Prevalence of Gastroesophageal Reflux Disease Symptoms in Infants and Children: A Systematic Review. Issue 6 (June 2019) - Singendonk, Maartje; Goudswaard, Eline; Langendam, Miranda; van Wijk, Michiel; van Etten-Jamaludin, Faridi; Benninga, Marc; Tabbers, Merit
ABSTRACT: Objectives: Gastroesophageal reflux disease (GERD) is defined as gastroesophageal reflux causing troublesome symptoms or complications. In this study we reviewed the literature regarding the prevalence of GERD symptoms in infants and children. Methods: Databases of PubMed, EMBASE, and Cochrane were systematically searched from inception to June 26, 2018. English-written studies based on birth cohort, school-based, or general population samples of ≥50 children aged 0 to 21 years were included. Convenience samples were excluded. Results: In total, 3581 unique studies were found, of which 25 studies (11 in infants and 14 in children) were included with data on the prevalence of GERD symptoms comprising a total population of 487, 969 children. In infants (0–18 months), GERD symptoms are present in more than a quarter of infants on a daily basis and show a steady decline in frequency with almost complete disappearance of symptoms at the age of 12 months. In children older than 18 months, GERD symptoms show large variation in prevalence between studies (range 0%-38% of study population) and overall, are present in >10% and in 25% on respectively a weekly and monthly basis. Of the risk factors assessed, higher body mass index and the use of alcohol and tobacco were associated with higher GERD symptom prevalence. Conclusions: This systematic review demonstrates that the reported prevalence of GERD symptoms varies considerably, depending on method of data collection and criteria used to define symptoms. Nevertheless, the high reported prevalence rates support better investment of resources and educational campaigns focused on prevention. Abstract : Supplemental Digital Content is available in the text